(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Trees are essential for human and environmental health as they provide oxygen, store carbon dioxide, and filter atmospheric air. In Uzbekistan, every year millions of dollars are invested by large-scale national afforestation programs for planting trees in arid and semi-arid regions. Even though planting targets are met, survival targets are not. Yashil Makon, the government’s initiative, targets one billion tree plantings by 2026, yet Daryo.uz (2022) documents the death of 2.4 million saplings in a single spring season mainly due to irrigation failure and the absence of post-planting accountability mechanisms. This article examines this issue in Uzbekistan and comparable arid regions and proposes a digital intervention model to address it.